An efficient solution procedure for elastohydrodynamic contact problems considering structural dynamics - Schmidt, Jan Henrik (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2018)
This work presents an efficient solution procedure for the elastohydrodynamic (EHD) contact problem considering structural dynamics. The contact bodies are modeled using reduced finite element models. Singly diagonal implicit Runge-Kutta (SDIRK) methods are used for adaptive time integration. The structural model is coupled with the nonlinear Reynolds Equation using a monolithic coupling approach. Finally, a reduced order model of the complete nonlinear coupled problem is constructed.